„Nie ma nic ważniejszego od religii, nic wznioślejszego od wiary” (Epistula 72, 12). Wiara w świetle listów św. Ambrożego - Wysocki, Marcin (Vox Patrum, 2013)
The presented paper discusses the issue of faith in St. Ambrose’s letters. According to him, there is nothing more important than faith and therefore he refers repeatedly in his correspondence to various issues related to faith. So Ambrose’s letters are the perfect practical complement to his dogmatic and exegetical works. The above article on the basis of the reading of his letters shows the faith as a gift to be developed and improved, having the source in the Scriptures; richness of faith and its reference to other virtues and the Christian faith in relation to Jews and Gentiles are shown as well.